Saúde mental, gênero, acolhimento e participação: uma experiência de cuidado em terapia ocupacional com duas adolescentes - Rosa, Gabriela Esquitini (Universidade Federal de São Carlos, 2025)
Introduction: Comprehensive healthcare for adolescents is a constitutional right in Brazil, reinforced by policies such as the Statute of the Child and Adolescent (ECA) and the Psychosocial Care Network, which guide intersectoral action and the adoption of humanized mental health practices. Despite these advances, adolescents, especially girls, still face significant challenges, including structural violence and limited access to sensitive, context-aware care. Considering the impact of gender-based oppression on the mental health of adolescent girls, Occupational Therapy integrates clinical practice with gender-based social markers and the principles of Psychosocial Care. Objective: This study aims to report the experience of an Occupational Therapy student in an interprofessional service for comprehensive adolescent care, in which she was able to develop individualized therapeutic processes with two adolescent girls who were victims of violence and presented mental health demands. In addition to describing the practical experience, the report also seeks to reflect on the challenges and potentialities of promoting integral care, with emphasis on gender-related issues and their implications for mental health. Method: The methodology consisted of the systematization of individual sessions carried out between June and November 2024, totaling 22 encounters. Activities were structured based on Occupational Therapy practices and guided by the concepts of human activity and life production, with a focus on qualified listening, valuing subjectivity, and strengthening adolescents' autonomy. Field notes were organized into logs and analyzed through the articulation between extension practice and theoretical frameworks from Psychosocial Care and gender studies. Results: Through meaningful and care-mediating activities—such as slime making, painting, self-care practices, bracelet making, origami, body map construction, and territorial engagement (visits to an ice cream shop and the municipal ecological park)—it was possible to establish therapeutic bonds, support emotional expression, and foster reflection on topics such as family relationships, experiences of violence, life projects, daily routines, and school or service-based interactions. Final Considerations: The student’s experience revealed that Occupational Therapy care, when guided by ethical-political and feminist principles, can serve as a tool for resistance, transformation, and the recognition of historically silenced subjectivities.
Mental health, gender, support, and participation: an occupational therapy care experience with two adolescent girls
Keywords: Saúde mental; Gênero; Terapia ocupacional; Adolescência; Processos de cuidado; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL